2022
DOI: 10.21428/cb6ab371.2ef20c24
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Prison TikTok”: Incarcerated Life Shared on Social Media

Abstract: Different areas of the criminal justice system interact with social media, but not much is known about how those incarcerated may be using it. A thematic analysis of "Prison TikTok" videos was conducted in order to gain a better understanding of what those incarcerated are sharing. The most represented themes in the sample are performance, food, prison, and pains of imprisonment. Performance and food demonstrate creativity within the sample, and highlight how those incarcerated may be looking for creative outl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…As cell phones have become smaller and more sophisticated, they are capable of accessing social media platforms and other mobile apps. Today, prisoners actively record and post TikTok videos under the hashtag #PrisonTikTok, a popular content category on the platform with over 3 billion views, to share their lived experiences with incarceration including recording trending dances and showing how to prepare prison meals [ 19 - 22 ]. However, the use of TikTok to promote K2/Spice-related content is not well understood, though prior studies have identified content on other social media platforms not related to the incarcerated population [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As cell phones have become smaller and more sophisticated, they are capable of accessing social media platforms and other mobile apps. Today, prisoners actively record and post TikTok videos under the hashtag #PrisonTikTok, a popular content category on the platform with over 3 billion views, to share their lived experiences with incarceration including recording trending dances and showing how to prepare prison meals [ 19 - 22 ]. However, the use of TikTok to promote K2/Spice-related content is not well understood, though prior studies have identified content on other social media platforms not related to the incarcerated population [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%